Melatonin inhibits apoptosis and improves the developmental potential of vitrified bovine oocytes - Zhao, Xue-Ming; Hao, Hai-Sheng; Du, Wei-Hua; Zhao, Shan-Jiang; Wang, Hao-Yu; Wang, Na; Wang, Dong; Liu, Yan; Qin, Tong; Zhu, Hua-Bin (Journal of pineal research, 2016)
Vitrification of oocytes has been shown to be closely associated with increased levels of reactive oxygen species (ROS) and apoptotic events. However, little information is available the effect of melatonin on the ROS levels and apoptotic events in vitrified oocytes. Therefore, we studied the effect of melatonin on ROS and apoptotic events in vitrified bovine oocytes by supplementing vitrification solution or in vitro maturation (IVM) and vitrification solution with 10−9 m melatonin. We analyzed the ROS, mitochondrial Ca2+ (mCa2+) and membrane potential (ΔΨm), externalization of phosphatidylserine (PS), caspase‐3 activation, DNA fragmentation, mRNA expression levels of Bax and Bcl2 l1, and developmental potential of vitrified bovine oocytes. Vitrified bovine oocytes exhibited increased levels of ROS, mCa2+, Bax mRNA, and caspase‐3 protein and higher rates of PS externalization and DNA fragmentation, and decreased ΔΨm and Bcl2 l1 mRNA expression level. However, melatonin supplementation in vitrification solution or IVM and vitrification solution significantly decreased the levels of ROS, mCa2+, Bax mRNA expression, and caspase‐3 protein, and PS externalization and DNA fragmentation rates, and increased the ΔΨm and Bcl2 l1 mRNA expression level in vitrified oocytes, resulting in an increased developmental ability of vitrified bovine oocytes after parthenogenetic activation. The developmental ability of vitrified oocytes with melatonin supplementation in IVM and vitrification solution was similar to that of fresh ones. This study showed that supplementing the IVM and vitrification medium or vitrification medium with 10−9 m melatonin significantly decreased the ROS level and inhibited apoptotic events of vitrified bovine oocytes, consequently increasing their developmental potential.